Ulama dalam Penguatan Politik Identitas Perspektif Al-Qur’an - Nafilah Sulfa (IAIN Madura, 2020)
‘Ulama are commanding religious figures with far-reaching knowledge; however, currently the term ‘ulama is distorted by unscrupulous people. Frequently, Ulama’s behaviors do not reflect their prestige as Prophet’s heir even though having a number of fanatical adherents. Their fatwa has authoritative influence in establishing post-truth narration. It can cause a horizontal gap and segregation in society if their fatwas are not true. This crisis affected by the increase of identity politics during pre-post political contestation. Meanwhile, the hugest disadvantages are beared by whose tend to believe in their thoughts and behaviors. We analyzed this phenomenon from the perspective of the Qur'an on the meaning of the term ‘ulama and their role in identity politics involvement. We used sociological-normative and descriptive-phenomenological methods to reread some related verses. This study showed, for example, refered to Q.S. Ali ‘Imran (3): 104, ‘ulama are allowed to have an active and positive role in the sphere of politics.